Positive Impact Forestry : a Sustainable Approach to Managing Woodlands. - McEvoy, Thomas J. (Island Press, 2010)
Positive Impact Forestry is a primer for private woodland owners and their managers on managing their land and forests to protect both ecological and economic vitality. Moving beyond the concept of "low impact forestry," Thom McEvoy brings together the latest scientific understanding and insights to describe an approach to managing forests that meets the needs of landowners while at the same time maintaining the integrity of forest ecosystems. "Positive impact forestry" emphasizes forestry's potential to achieve sustainable benefits both now and into the future, with long-term investment superseding short-term gain, and the needs of families -- especially future generations -- exceeding those of individuals. Thom McEvoy offers a thorough discussion of silvicultural basics, synthesizing and explaining the current state of forestry science on topics such as forest soils, tree roots, form and function in trees, and the effects of different harvesting methods on trees, soil organisms, and sites. He also offers invaluable advice on financial, legal, and management issues, ranging from finding the right forestry professionals to managing for products other than timber to passing forest lands and management legacies on to future generations. Positive Impact Forestry helps readers understand the impacts of deliberate human activities on forests and offers viable strategies that provide benefits without damaging ecosystems. It speaks directly to private forest owners and their advisers and represents an innovative guide for anyone concerned with protecting forest ecosystems, timber production, land management, and the long-term health of forests.